Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach--in which pornography is defined as sex discrimination and therefore a violation of civil rights--would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance--what it is, what it does, what it means, how it works. Answers to the lies about it--lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." --from Pornography and Civil Rights
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

The sexual contract - Pateman, Carole (Standford University Press, 1988)
In this remarkably original work of political philosophy, one of today's foremost feminist theorist challenges the way contemporary society functions by questioning the standard interpretation of an idea that is deeply embedded in American and British political thought: that our rights and freedoms derive from the social contract explicated by Locke, Hobbes, and Rousseau and interpreted in the United States by the Founding Fathers.
Keywords: 1900-1999; 1980-1989; amériques; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; incontournable; philosophie politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; théories féministes; états-unis

Maria W. Stewart, America's first Black woman political writer : essays and speeches - Stewart, Maria W. (Indiana University Press., 1987)
En rassemblant et en présentant les œuvres de Stewart, Richardson offre aux lecteurices l'occasion d'étudier les pensées et les paroles de cette influente militante noire, précurseuse de Frederick Douglass et de Sojourner Truth et première noire américaine à donner des conférences pour la défense des droits des femmes, la plaçant dans le contexte du mouvement abolitionniste tourbillonnant.
Keywords: 1800-1899; afro-féminisme; amériques; antiesclavagisme; approches et analyses; cours; discipline; droits des femmes*; fem1000; femmes* afro-américaines; féminismes noirs; histoire; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

L'émergence d'une culture au féminin - Zavalloni, Marisa (Collection Femmes, 1987)
Comment définir une culture au féminin ? Quelles formes peut-elle prendre dans les sciences sociales, la littérature, la philosophie et l’art ? Les recherches présentées dans ce recueil, par leur approche analytique, humoristique, caustique, radicale ou poétique, apparaitront comme la poursuite du même idéal, créer une société dans laquelle « les femmes s’appartiennent totalement, non seulement physiquement, mais symboliquement ».
Keywords: 1900-1999; 1980-1989; amériques; cours; droits des femmes*; fem1000; interdisciplinarité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études culturelles

Stratégies des femmes - Pasquier, Marie Claire (Tierce, 1984)
Stratégies des pouvoirs, stratégies des femmes pour leur résister : c’est toujours la même chose et c’est toujours différent. Lieux concrets et formes subtiles d’oppression, qu’il s’agisse d’institutions, d’organisations ou de discours. Insurrections héroïques des femmes, actions d’éclat ou mouvements souterrains méconnus des historiens, tentatives suivies d’échec. Alliances inattendues, effets imprévisibles, paradoxes. Le livre fait apparaître l’impossibilité de s’en tenir à des catégories massives, tranchées, telles que « la droite », « la gauche », « la femme ouvrière », « la bourgeoise », « la lesbienne », « la catholique », « la féministe ». À la place, une irréductible pluralité des représentations, des actions, des réactions. 4è de couverture
Keywords: anthologie; approches et analyses; citoyenneté; cours; discipline; droits des femmes*; fem1000; histoire; pratiques féministes; premier cycle; rapports sociaux de sexe; sciences humaines; thématiques

Chapitre 2. Le mouvement anti-esclavagiste et la naissance des droits des femmes. - Davis, Angela Yvonne (Femmes, race et classe, 1983)
Etude socio-historique de la condition des femmes noires aux Etats-Unis; aspect particulier de l'esclavage des femmes noires; persistance des problèmes après l'abolition de l'esclavage.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; corps; cours; discipline; droits des femmes*; esclavagisme; féminisme afroaméricain; féminismes noirs; histoire et politique; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; états-unis

Nous sommes le produit d’un contexte - O'Leary, Véronique; St-Pierre, Josée.; Toupin, Louise (Québécoises deboutte! Tome 1. Une Anthologie de textes du Front de libération des femmes (1969-1971) et du Centre des femmes (1972-1975)., 1983)
Le volume 1 (212 p.) comprend des tracts, documents internes, manifestes et lettres diffusées par les deux groupes entre 1969 et 1975, de même qu'un aperçu de la couverture de presse dont ils bénéficièrent à l'époque. Le volume 2 (377 p.) reprend la collection complète du journal ##Québécoises deboutte## publié entre 1972 et 1975, par le Centre des femmes; on y a ajouté des tables rondes.
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; histoire et politique; inégalités; militance; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques

La citoyenne : articles de 1881-1891 - Auclert, Hubertine (Syros, 1982)
Keywords: 1800-1899; cours; droits des femmes*; europe; fem1000; france; pratiques féministes; premier cycle; périodes historiques; régions géographiques; thématiques

Ce que veulent les femmes : articles et conférences de 1869 à 1891 - Deraismes, Maria (Mémoire des femmes, 1980)
Keywords: 1800-1899; conflit; cours; droits des femmes*; europe; fem1000; france; histoire et politique; militance; premier cycle; périodes historiques; régions géographiques; thématiques